2022
DOI: 10.21315/aamj2022.27.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Green innovation on firm value with financial performance as mediating variable: Evidence of the mining industry

Abstract: The topic of environmental performance is gaining much attention from academics and politics when it is associated with each country’s policies regarding environmental problems. Unfortunately, the comprehensive studies to observe this case become rare, therefore this study is aimed to investigate the direct and indirect effect of green innovation on firm value based on financial performance as the mediating variable. Mining companies which participate in Corporate Performance Rating Assessment (PROPER) listed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Organizations must develop a green innovation strategy embodied in a green organizational entity to obtain environmental and organizational legitimization and improve innovation performance [23]. Therefore, SMEs often need a more comprehensive view of the future path of innovation and are likely to address green issues appropriately [27,34,35].…”
Section: The Effect Of Product Uniqueness On Green Management and Sus...mentioning
confidence: 99%
“…Organizations must develop a green innovation strategy embodied in a green organizational entity to obtain environmental and organizational legitimization and improve innovation performance [23]. Therefore, SMEs often need a more comprehensive view of the future path of innovation and are likely to address green issues appropriately [27,34,35].…”
Section: The Effect Of Product Uniqueness On Green Management and Sus...mentioning
confidence: 99%
“…2.1.2 | Studies on the positive impact of green innovation, including mediating variable Fernando et al (2019) showed that green innovation has a strong influence on sustainable performance mediated by service innovation capabilities. Khusnah et al (2021), Asni and Agustia (2022), and Yuniarti et al (2022) found that financial performance mediates the impact of green innovation on firm value. Zheng et al (2022) found that green innovation can significantly improve the ESG performance, both green innovation and ESG performance can improve the financial performances, and ESG performance plays an indirect mediating role in promoting green innovation on financial performance.…”
Section: Studies On the Positive Impact Of Green Innovationmentioning
confidence: 99%
“…Fernando et al (2019) showed that green innovation has a strong influence on sustainable performance mediated by service innovation capabilities . Khusnah et al (2021), Asni and Agustia (2022), and Yuniarti et al (2022) found that financial performance mediates the impact of green innovation on firm value .…”
Section: Literature Reviewmentioning
confidence: 99%
“…And applied to the entire business process (Mariyamah and Handayani, 2020;Dewi and Rahmianingsih, 2020). Even though there is no guarantee of certainty regarding the results obtained, the many benefits of innovation that can be obtained will be far more valuable than the costs incurred (Agustia et al, 2019), so that investor interest will focus on the company because they believe that the company is focused on environmental sustainability in the future (Yuniarti et al, 2022). However, creating environmentally friendly innovation is not an easy job, to make it happen requires quite a lot of money and companies need accurate, detailed and relevant information so EMA needs to be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to research conducted by Yuniarti et al (2022) which suggests using different measurements of green innovation, this research applies measurements carried out by Agustia et al (2019), Damas and Tarisa (2022) using the Green Innovation Checklist The index and object carried out are by using a manufacturing company. This is because according to environmental problems it is mainly caused by manufacturing companies and because manufacturing has a big impact on sustainable and environmentally friendly economic growth (Lin, H, Zeng 2017).…”
Section: Introductionmentioning
confidence: 99%